A population-based study on peanut, tree nut, fish, shellfish, and sesame allergy prevalence in Canada - Moshe Ben‐Shoshan; Daniel W. Harrington; Lianne Soller; Joseph Fragapane; Lawrence Joseph; Yvan St. Pierre; Samuel Benrejeb Godefroy; Susan Elliot; Ann E. Clarke (2010)
Recent studies suggest an increased prevalence of food-induced allergy and an increased incidence of food-related anaphylaxis. However, prevalence estimates of food allergies vary considerably between studies.To determine the prevalence of peanut, tree nut, fish, shellfish, and sesame allergy in Canada.Using comparable methodology to Sicherer et al in the United States in 2002, we performed a cross-Canada, random telephone survey. Food allergy was defined as perceived (based on self-report), probable (based on convincing history or self-report of physician diagnosis), or confirmed (based on history and evidence of confirmatory tests).Of 10,596 households surveyed in 2008 and 2009, 3666 responded (34.6% participation rate), of which 3613 completed the entire interview, representing 9667 individuals. The prevalence of perceived peanut allergy was 1.00% (95% CI, 0.80%-1.20%); tree nut, 1.22% (95% CI, 1.00%-1.44%); fish, 0.51% (95% CI, 0.37%-0.65%); shellfish, 1.60% (95% CI, 1.35%-1.86%); and sesame, 0.10% (95% CI, 0.04%-0.17%). The prevalence of probable allergy was 0.93% (95% CI, 0.74%-1.12%); 1.14% (95% CI, 0.92%-1.35%); 0.48% (95% CI, 0.34%-0.61%); 1.42% (95% CI, 1.18%-1.66%); and 0.09% (95% CI, 0.03%-0.15%), respectively. Because of the infrequency of confirmatory tests and the difficulty in obtaining results if performed, the prevalence of confirmed allergy was much lower.This is the first nationwide Canadian study to determine the prevalence of severe food allergies. Our results indicate disparities between perceived and confirmed food allergy that might contribute to the wide range of published prevalence estimates.